Exchange Rate Volatility And Non-Oil Imports In Nigeria: A Cointegration Analysis - Inam, Uduakobong S.; Oscar, Williams Anthony (Advances in Social Sciences Research Journal, 2017)
This paper analyses the relationship between exchange rate volatility and non-oil imports in Nigeria using annual data covering the period of 1970 to 2015. Specifically, it seeks to: investigate the existence of a long run relationship between exchange rate volatility and non-oil imports in Nigeria; and determine the nature of the causal relationships between exchange rate volatility and non-oil imports in Nigeria. The study employed the Johansen test of Cointegration, Error Correction Model, and the Granger Causality test to achieve the objectives. The findings reveal that: there exists a long run relationship between exchange rate volatility and non-oil import,; exchange rate does not granger cause the movements in non-oil imports. The study recommends amongst others that the exchange rate should be closely monitored and effectively managed. Specifically, policies that seek to maintain the exchange rate at a very minimal level should be promoted. The government and relevant monetary authorities should seek to employ and implement policies that stabilize the exchange rate given its significant impact on non-oil imports in Nigeria.